QSAR Studies of Nitrobenzothiazole Derivatives as Antimalarial Agents - Hadanu, Ruslin; Adelin, La; Sutapa, I Wayan (UI Scholars Hub, 2018)
Quantitative Structure and Activity Relationship (QSAR) analyses were carried out for a series of 13 nitrobenzothiazole derivatives as antimalarial compounds to find out the structural relationship of their antimalarial activities against the W2 Plasmodium falciparum strain. The electronic descriptors have been determined usingthe atomic net charges (q), dipole moment (μ), ELUMO, EHOMO, polarizability (α) and Log P. Inaddition, the descriptors were calculated through Hyper Chem for Windows 8.0 using the PM3 semi-empirical method. The antimalarial activities (IC50) were taken fromliterature [1]. Furthermore, the QSAR model was determined by multiple linear regression (MLR) approach, giving equation model of QSAR: Log IC50 = 41.483 + 54.812 (qC2) – 50.058 (qS3) + 416.766 (qC4) + 440.734 (qC5) – 754.213 (qC7) – 73.721 (qC8) + 246.715 (qC9) + 0.551 (μ) – 13.269 (EHOMO) – 3.404 (ELUMO) + 0.042 (α) + 0.107 (LogP). The most statistically significant QSAR model with correlation coefficients n = 13, (r) = 1.00, (r2) = 1.00, SE = 0, and PRESS = 3.40 were developed by MLR. Based on the model of the above QSAR equation 43 new nitrobenzothiazole derivatives were modeled and 24 of these compounds showed high antimalarial activity. It isrecommended that these are synthesized for further investigation 4 new compounds (45, 49, 52 and 55) show equivalent activity to that achieved with chloroquine antimalarial drugs.